The Thai education system and the challenges in developing human capital: problems with teaching and learning, rote memorization, the competitive examination system, and international competitiveness. - Hawhan, Prasub (Thai Social Science Journal, 2026)
This article analyzes the key challenges in the Thai education system that impact human capital development, focusing on the issues of rote learning, competitive examination systems, and their effects on students’ ability to compete internationally. The study highlights the persistence of traditional teaching methods centered on memorization and high-stakes testing, which hinder the development of critical thinking, creativity, and problem-solving skills. International assessments such as PISA and TIMSS reveal that Thai students consistently score below average in several key areas, reflecting the limitations of the education system in preparing students for the demands of the 21st century. The misalignment between education policies and labor market needs further restricts the growth of quality human capital in Thailand.The article proposes policy recommendations aimed at reforming teaching approaches to emphasize analytical and creative skills, improving teacher quality and educational resources, and revising examination systems to reduce stress and encourage deeper learning. It also stresses the importance of digital literacy and media competence to equip youth for the challenges of the modern world.